Proposing the Clinical Inventory of Sleep Quality (2016)
Introduction The aim of the study was to propose the Clinical Inventory of Sleep Quality (CISQ), and compared it with the Pittsburgh sleep quality index (PSQI). Methods We studied 400 subjects with the CISQ. Cronbach's alpha coefficient was calculated to measure the reliability, and to determine the concurrent validity, a Canonical correlation analysis was performed. At next, we used an exploratory and confirmatory Factorial analysis with Varimax rotation for validity construct calculation. Results Cronbach alpha coefficient of the scale was significantly strong (a=0.81). Canonic correlation was=0.93, suggesting that data proved that the CISQ and PSQI are measuring identical subject. Confirmatory Factorial analysis model grouped items of the scale in four factors: 1. Daytime symptoms, 2. Nocturnal symptoms, 3. Sleep disordered breathing symptoms, and 4. Sleep-related movement disorders symptoms. We proposed five categories to score CISQ in a range of 0-52 points, as follows: Good quality of sleep, Mild bad sleep quality, Moderate bad sleep quality, Severe bad sleep quality, and Profound bad sleep quality. Conclusion CISQ is a promising tool to measure sleep quality and deserve more research to confirm its utility. © 2016 Brazilian Association of Sleep Production and Hosting by Elsevier B.V.